The impact of a "narrative interview" intervention in oncology. A study protocol for a feasibility study.: A study protocol about "narrative interview" intervention in oncology. - Artioli, Giovanna; Foà, Chiara; Bertuol, Maria; Benzi, Linda; Deiana, Laura; Meneghetti, Chiara; Neri, Cecilia; Pigoni, Laura; Zanotti, Martina; Sarli , Leopoldo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Oncological diagnosis determines a biographical breakdown and requires the person to adapt to the disease. If patients, after diagnosis, ask professionals for ‘compassionate care’, research on these issues is still underdeveloped. There are currently no studies that use the narrative interview as an intervention tool. The objectives of the study are to evaluate: (1) the feasibility of the narrative interview intervention on cancer patients in the first diagnosis; (2) the impact of the narrative medicine intervention on the patient’s self-perception, his psychological distress and adaptation to the disease. Methods. It is a mixed-method study, with an intervention (narrative interview) and quantitative evaluation before/after intervention and qualitative evaluation post-intervention (reflective writing). The analysis will use the Psychological Distress Inventory scale for the assessment of psychological distress and the Mini-Mental Adjustment to Cancer Scale for the assessment of disease adaptation. Adult patients, with oncological pathology will be recruited one month after the communication of the diagnosis, regardless of the type of tumor. The Wilcoxon test for paired data will be used to verify pre-post-intervention differences. The ‘reflective writings’ will be subjected to thematic analysis. Discussion and conclusion. The study evaluates the feasibility of the narrative interview intervention as a primary outcome. Secondly, the impact of the intervention is assessed in relation to: a) identification of risk or protective factors on psychological distress and adaptation to the disease; b) re-elaboration of the patient’s experiences and experiences related to his/her own illness.